Psychiatric mental health nursing - Fortinash, Katherine M. (St. Louis, Missouri : Elsevier Mosby, 2012)
The fifth edition of Psychiatric Mental Health Nursing provides up-to-date, comprehensive, and straightforward coverage of psychiatric nursing. Using a balanced nursing-medical approach and presenting strong baseline coverage of the DSM-IV-TR and related treatments, this book continues to focus on what nurses actually do. Fundamental concepts such as psychobiology, legal and ethical implications, and cultural and spiritual issues are introduced early on, followed by chapters devoted to specific psychiatric treatment modalities and other relevant issues --Ohiolink Catalog